2008
DOI: 10.1037/0022-3514.94.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Modeling support provision in intimate relationships.

Abstract: Whereas supportive interactions are usually studied from the perspective of recipients alone, the authors used a dyadic design to incorporate the perspectives of both provider and recipient. In 2 daily diary studies, the authors modeled provider reports of support provision in intimate dyads over several weeks. The 1st involved couples experiencing daily stressors (n ϭ 79); the 2nd involved couples experiencing a major professional stressor (n ϭ 196). The authors hypothesized that factors relating to (a) recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
156
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(174 citation statements)
references
References 77 publications
15
156
3
Order By: Relevance
“…Past research has shown, for example, that positive relationship feelings predict caring behavior not only in laboratory experiments (Rusbult, Verette, Whitney, Slovik, & Lipkus, 1991;Tran & Simpson, 2009), but also in daily diary studies (Iida et al, 2008;Laurenceau, Barrett, & Rovine, 2005). On the surface, this would appear to be in conflict with the findings of the present studies, as daily behaviors seemingly fit in the long-term category.…”
Section: Short-term and Long Term Pro-relational Behaviorcontrasting
confidence: 75%
See 1 more Smart Citation
“…Past research has shown, for example, that positive relationship feelings predict caring behavior not only in laboratory experiments (Rusbult, Verette, Whitney, Slovik, & Lipkus, 1991;Tran & Simpson, 2009), but also in daily diary studies (Iida et al, 2008;Laurenceau, Barrett, & Rovine, 2005). On the surface, this would appear to be in conflict with the findings of the present studies, as daily behaviors seemingly fit in the long-term category.…”
Section: Short-term and Long Term Pro-relational Behaviorcontrasting
confidence: 75%
“…On the one hand, there is empirical support for the idea that positive relationship feelings can motivate costly and effortful behavior on behalf of a loved one. Studies find that people with strong feelings of satisfaction in the relationship engage in more support-provision and partner-caregiving than do people who are less satisfied (Feeney & Collins, 2003;Iida, Seidman, Shrout, Fujita, & Bolger, 2008). Individuals who describe themselves as close and committed are more likely to feel empathy for a relationship partner and to forgive the partner when he or she transgresses (Finkel, Rusbult, Kumashiro, & Hannon, 2002).…”
mentioning
confidence: 93%
“…The fact that spouses were not included in the current study is an important limitation, and future research is needed that includes both members of the dyad [58]. Although the current study included a comprehensive battery of variables shown to impact support satisfaction in past research, fatigue was measured only once.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore one reason why marriage affords women less of a benefit than it affords men might well be that they need the marriage less than do men. They have more mutually supportive other relationships which provide opportunities to them both to be caring, which itself can generate better emotional states (Williamson and Clark 1989) and to be cared for (Iida et al 2008). Note that the existence of these other relationships can also partly explain why, following the death of a spouse, women seem to fare better than do men health-wise (Stroebe et al 2001).…”
Section: Consider Processes Occurring Outside Marriages As Well As Inmentioning
confidence: 87%